Teacher Training in Austria in the Last Decade—The Development of and Challenges for an Inclusive School System - Paudel, Florentine; Subasi Singh, Seyda (Frontiers in Education, 2020)
This paper outlines the journey of reforming teacher training in Austria from special education to inclusive education in the light of recent political developments, international legislation and recommendations. After a historical overview of special education teacher training, this study discusses the developments that had an impact on the current teacher training for inclusive education in Austria. On the basis of content analysis of relevant policy documents, regulations, reports, and statements, the paper analyzes the impact of the political changes in the country as well as of international movements on the curriculum, policies, and practices for teacher training for special needs education and inclusive education over the course of time. The text-based analysis revealed that while Austria has diligently followed international recommendations and agreements, it was nevertheless criticized for its failure to successfully implement already piloted practices on a large scale.